2015
DOI: 10.3354/meps11429
|View full text |Cite
|
Sign up to set email alerts
|

Microbial food web structural and functional responses to oyster and fish as top predators

Abstract: The impact of fish and oysters on components of the pelagic microbial food web (MFW) was studied in a 10 d mesocosm experiment using Mediterranean coastal waters. Two mesocosms contained natural water only ('Controls'), 2 contained natural water with Crassostrea gigas ('Oyster'), and 2 contained natural water with Atherina spp. ('Fish'). Abundances and biomasses of microorganisms (viruses, bacteria, phytoplankton, heterotrophic flagellates, and ciliates) were measured to estimate their contribution to the tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
12
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 51 publications
8
12
1
Order By: Relevance
“…In parallel to oyster mortality, temporal variability of nutrient concentrations and PMC were explored. Dissolved Inorganic Nitrogen (DIN), Phosphorus (DIP) and N:P ratio were low and consistent with those already observed in the Thau lagoon , Mostajir et al 2015. The Thau lagoon was in N limitation according to the criteria of Justic et al 1995 (DIN <1 μM and DIN/DIP <10), as already observed in spring .…”
Section: Accepted Manuscriptsupporting
confidence: 87%
See 3 more Smart Citations
“…In parallel to oyster mortality, temporal variability of nutrient concentrations and PMC were explored. Dissolved Inorganic Nitrogen (DIN), Phosphorus (DIP) and N:P ratio were low and consistent with those already observed in the Thau lagoon , Mostajir et al 2015. The Thau lagoon was in N limitation according to the criteria of Justic et al 1995 (DIN <1 μM and DIN/DIP <10), as already observed in spring .…”
Section: Accepted Manuscriptsupporting
confidence: 87%
“…The phytoplankton Chla biomasses, heterotrophic prokaryote abundances and biovolumes of HF and ciliates were converted to equivalent carbon (C) biomass as in Mostajir et al (2015). Chla data were converted to C biomass using a value of 57 (Latasa et al 2005), as carried out previously in a mesocosm experiment in the Thau lagoon (Vidussi et al 2011).…”
Section: Estimating Carbon Biomass For Planktonic Microbial Componentsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the same way, in a mesocosm experiment in Mediterranean coastal waters, Mostajir et al . () demonstrated that oyster culture induces lowers autotrophy‐heterotrophy ratio, highlighting the occurrence of a profound alteration in trophic food‐web functioning. However, consequences for planktonic food‐web alteration are still poorly documented and further investigations are needed.…”
Section: Grazing Pressure Induced By Shellfish Farming: a Source Of Pmentioning
confidence: 99%